Hematological Analysis of Red Bader Fish (Barbonymus altus) as a Biomarker in Assessing Pollution Status in Brantas River, Surabaya, East Java - Arief Farhan Kurniawan Anasiru; Asus Maizar Suryanto Hertika; Uun Yanuhar (Jurnal Penelitian Pendidikan IPA, 2024)
The Brantas River has many functions for both humans and the aquatic organisms in it. The type of fish that is often found in the Brantas River in Surabaya is the red bader fish (Barbonymus altus). Hematology is a sensitive parameter and can be used as a marker in assessing water conditions. The aim of this research is to analyze the hematological profile of red bader fish (Barbonymus altus) to assess the condition of the Brantas River, Surabaya. The research was carried out at 3 locations on the Brantas River in Surabaya with 3 sampling times with an interval of 1 month starting in January – March 2022. The parameters observed were water quality (temperature, TSS, TDS, pH, DO, BOD, ammonia and heavy metals Hg) and hematological parameters (erythrocytes, hemoglobin, hematocrit, leukocytes and micronuclei). Analysis of the relationship between water quality parameters and hematology using the Correspondence Correlation Analysis (CCA) method. The results show that there are water quality parameters that do not meet quality standards and there are abnormal hematological parameters. CCA analysis shows that there is a correlation between water quality and hematological parameters with moderate concentrations (erythrocytes, hemoglobin and hematocrit) and strong concentrations (leukocytes and micronuclei).